Sherlock Holmes Between Homogeneity Tests: Detection Power Based on Profitability Ratios in the V4 Region - Pavol Durana; Roman Blazek; Erika Kovalova (Stats)
Profitability reveals the key financial ratios that ensure the long-term sustainability of an enterprise’s ability to invest in further growth. Without knowledge of the course of development, particularly changes in profitability, enterprises face financial difficulties that threaten their existence. Although the homogeneity tests serve as a reliable tool for identifying changes, their application in financial management often receives insufficient attention. The aim of this research is to evaluate the detection power of homogeneity tests and identify the one with the highest ability based on testing changes in the development of profitability ratios across sectors in the Visegrad Four. Buishand’s test, Pettitt’s test, the SNHT, and the von Neumann test were run for 8671 enterprises during 2016–2021 and gained from Moody’s Orbis. Comparison tables for ROA, ROC, ROE, ROS, ROR, and ROW using Monte Carlo simulation with a million replications identified the number of Slovak, Czech, Polish, and Hungarian enterprises in which heterogeneity was divided according to the Nomenclature of Economic Activities, NACE. The SNHT disclosed the greatest number of changes in the development of all profitability ratios. The results validate the use of selected tests for ratio assessment. Furthermore, business agencies may replicate this approach to determine the economic situation and sector performance.